Pengaruh Transformational Leadership terhadap Work Engagement Pegawai PT PLN Unit Induk Distribusi Jawa Timur - Putri, Nisrina Kartika (Jejaring Administrasi Publik, 2024)
Transformational leadership, characterized by individuals leading and motivating their employees through exemplary behavior, significantly influences the work engagement of employees. Work engagement, representing an individual's positive attitude while working, plays a crucial role in organizational dynamics. This research focuses on examining the impact of transformational leadership on the work engagement of employees at PT PLN (Persero) Distribusi Jawa Timur, with a specific case study in the fields of communication, law, and administration. The study involves 21 subjects selected from a total population of 39 employees in the specified fields. Data collection utilizes Likert scale assessments, employing the MLQ scale for measuring transformational leadership and the UWES scale for assessing work engagement. Employing a quantitative approach, the findings of this research reveal a significant influence of transformational leadership on work engagement among employees in the specified fields of PT PLN (Persero) Unit Induk Distribusi Jawa Timur. This conclusion is supported by statistical analysis, particularly the Pearson correlation test, which indicates a correlation coefficient of 0.654 with a significance level of 0.05. Keywords: Transformational Leadership, Work Engagement